Are foreign private equity buyouts bad for workers? - Martin Olsson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2018)
The media often cast foreign private equity firms as villains who gamble with local jobs. We use detailed registry data from Sweden to show that foreign buyouts have not affected workers' labor market outcomes. But domestic buyouts have. They have increased unemployment incidence by a fifth, duration by a third, and lowered labor income by seven percent.
Keywords: G24; J20; 330; Buyouts; Cross-border; Employment; Foreign; LBOs; Private Equity; Workers